1981
DOI: 10.1042/bj1930469
|View full text |Cite
|
Sign up to set email alerts
|

The preparation and properties of folate-binding protein from cow's milk

Abstract: An improved affinity-chromatographic method for the preparation of folate-binding protein from cow's milk is described. Under dissociating conditions the protein appeared homogeneous in the ultracentrifuge, with a molecular weight of 35 000 +/- 1500, but it was heterogeneous on electrophoresis and ion-exchange chromatography and evidently consisted of several glycoproteins with similar molecular weights that all bound folic acid. Overall, the protein contained a high proportion of half-cystine (18 residues/mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
75
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 22 publications
8
75
1
Order By: Relevance
“…SALTER el al. (14) have determined the content of the individual carbohydrates in FBP and showed that approximately 40% is contributed by N-acetylglucosamine and N-acetylgalactosamine. These authors found a carbohydrate content of 10%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SALTER el al. (14) have determined the content of the individual carbohydrates in FBP and showed that approximately 40% is contributed by N-acetylglucosamine and N-acetylgalactosamine. These authors found a carbohydrate content of 10%.…”
Section: Discussionmentioning
confidence: 99%
“…SALTER et al (14) determined the molecular weight to 35.000 from sedimentation equilibrium studies. We are unable to explain the large discrepancy between our and their values but a difference in experimental technique was that they used 6 M-guanidinium chloride as solvent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These assays use folate binding protein (FBP) for analyte capture, which is typically a β -lactoglobulin isolated from cow ' s milk. These β -lactoglobulins will capture 5-methylTHF, as well as other forms of folate depending on pH [ 7 ]. These assays can be used to quantify folate both in serum and red blood cells.…”
Section: Introductionmentioning
confidence: 99%
“…In the fortified pasteurised milk, the amount of folic acid was 7.5 times higher than the amount of FBP (Table 3). According to Salter et al (1981), 1 molecule FBP binds 1 molecule of folate at pH 7.2. Thus, only a small amount of the added folic acid is expected to be bound to FBP in the fortified pasteurised milk.…”
Section: Discussionmentioning
confidence: 99%